2011
DOI: 10.1063/1.3630123
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and structural investigation of the role of both Mn and Mn oxide in the formation of manganese silicate barrier layers on SiO2

Abstract: In this study, Mn silicate (MnSiO 3 ) barrier layers were formed on thermally grown SiO 2 using both metallic Mn and oxidized Mn films, in order to investigate the role of oxygen in determining the extent of the interaction between the deposited Mn and the SiO 2 substrate. Using x-ray photoelectron spectroscopy, it has been shown that a metallic Mn film with an approximate thickness of 1 nm cannot be fully converted to Mn silicate following vacuum annealing to 500 C. Transmission electron microscopy (TEM) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 16 publications
8
38
0
Order By: Relevance
“…This would correspond to Mn in a purely +2 oxidation state. Given the composition profiles observed (Mn, Si, and O in the self-formed diffusion barrier region), it is suggested that the barrier is primarily composed of MnSiO 3 , which is in good agreement with the composition recently reported by Casey et al 17 for annealed ultrathin layers of pure metallic Mn on SiO 2 . The activity coefficients of Mn in Cu, especially for low concentrations, has been reported to be larger than unity, 18 which means that the solute atoms in the Mn(Cu) alloy will be expelled from the matrix if a more favorable chemical reaction can take place.…”
supporting
confidence: 78%
“…This would correspond to Mn in a purely +2 oxidation state. Given the composition profiles observed (Mn, Si, and O in the self-formed diffusion barrier region), it is suggested that the barrier is primarily composed of MnSiO 3 , which is in good agreement with the composition recently reported by Casey et al 17 for annealed ultrathin layers of pure metallic Mn on SiO 2 . The activity coefficients of Mn in Cu, especially for low concentrations, has been reported to be larger than unity, 18 which means that the solute atoms in the Mn(Cu) alloy will be expelled from the matrix if a more favorable chemical reaction can take place.…”
supporting
confidence: 78%
“…14, 15 Casey et al 15 have recently reported that the growth of Mn complex oxide layers on SiO 2 surfaces is self-limited by the presence of additional oxygen species, beyond that found within the SiO 2 layers. Therefore, in this study, a clear Mn complex oxide layer may not form due to the absence of excess oxygen species on the silicon oxide layer.…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, no clear chemical shift difference was obtained for the Cu-L, Mn-L, and O-K edges' spectra in any of the samples, and we found that no clear Mn complex oxide layer formed as reported by Otsuka et al 10 As mentioned previously, this result suggests that the absence of oxygen species beyond that found in the silicon oxide layer would have greatly limited the growth of a Mn complex oxide layer and most of Mn at the interface is in a metallic state in this study. 15 Instead, the Si-L…”
Section: Resultsmentioning
confidence: 99%
“…Post metallization annealing results in the expulsion of the alloying material from the bulk interconnect line towards all surrounding surfaces of the interconnect line, including the interface with the surrounding inter layer dielectric (ILD) [5]. As the alloying element reaches the Cu/ILD interface, it chemically reacts with the top few nanometres (~ 3nm) of the dielectric to form a stable metal silicate or metal oxide barrier [6] [7]. Aluminium has emerged as a possible alloying element to use in selfforming barrier layer applications due to its high solubility in Cu [8] and thermodynamic favourability to form a stable metal oxide layer [9].…”
Section: Introductionmentioning
confidence: 99%